Perancangan Game Edukasi Find the Vaccine tentang Virus COVID-19 sebagai Wawasan untuk Remaja - Baskoro, Sandy Yohan; Wardhana, Mitra Istiar; Samodra, Joko (Journal of Language Literature and Arts, 2023)
Banyak negara yang terjangkit pandemi COVID-19, Indonesia adalah salah satunya. Virus COVID-19 merupakan penyakit menular yang disebabkan oleh virus corona 2 (SARS-CoV-2) dan menyerang sistem pernapasan. Banyak remaja merasakan jenuh dan bosan dirumah akibat efek pandemi ini. Disisi lain mereka juga harus tetap belajar ditengah pandemi. Banyak media pembelajaran yang digunakan ditengah pandemi, salah satunya game edukasi. Tujuan perancangan game “Find the Vaccine” ini sebagai penambah wawasan sekaligus hiburan untuk para remaja. Metode yang digunakan adalah metode pra produksi, produksi, pasca produksi agar mendapat hasil yang maksimal. Tujuan selanjutnya adalah membangun game edukasi untuk memberikan wawasan tentang pencegahan penularan COVID-19 kepada remaja dengan menggunakan game engine Construct 2. Adapun hasil pengujian game ini menyatakan bahwa 70 persen responden menyatakan bahwa game ini baik dan layak dari sisi tampilan, gameplay dan user interfacenya. Kata kunci: game edukasi; COVID-19; pandemi Designing an Educational Game Find the Vaccine about COVID-19 Virus as Insight for Teenagers Many countries have been affected by the COVID-19 pandemic; Indonesia is one of them. The COVID-19 virus is an infectious disease caused by the corona virus 2 (SARS-CoV-2) and attacks the respiratory system. Many teenagers feel bored at home due to the effects of this pandemic. On the other hand, they also have to keep learning in the midst of a pandemic. Many learning media are used in the midst of a pandemic, one of which is educational games. The purpose of designing this “Find the Vaccine” game is to add insight as well as entertainment for teenagers. The method used is the method of pre-production, production, post-production in order to get maximum results and to build an educational game to provide insight into preventing the spread of COVID-19 to teenagers by using the game engine Construct 2. The results of testing this game stated that 70 percent of respondents stated that this game was good and worthy in terms of appearance, gameplay and user interface. Keywords: educational game; COVID-19; pandemic